Feminine Angst in the Poetry of Sylvia Plath - Syeed, Syed Aamir; Ali, Master Showkat (Journal of English Language and Literature (ISSN: 2368-2132), 2015)
Women have been struggling to liberate themselves from subjugation by their male counterparts from times immemorial. The various factors responsible for their suppression were misogyny, romantic glorification and patriarchy. Illogically romanticized, they are not permitted to play a significant role as independent, self-assured individuals and this was compounded by other unfair social, political and biological factors. As a result, they did not enjoy a contented position in society. History inclined to link man to wisdom and biological dominance and women were associated with confined concerns of household chores and childcare. This provoked some prominent women in America and England to launch a movement called feminism demanding equivalent rights and equal status for themselves. They also resisted the menacing power of the literature that portrayed a woman as a subordinate to patriarchy. To end this suppression and exploitation they set out to create a literature of their own. As such, most of the feminists got entangled in a twofold approach. On the one hand, they wanted an authentic voice to assert its sovereignty, and, on the other, to make their mark felt along gender defined lines, so as to mend laws governing their social, psychological and biological behaviour. Still, some of the women writers felt the brunt of male dominance and oppression so enormously that they developed the feelings of resentment and vengeance against them. In this, Sylvia Plath, a vigorous and highly competitive and self-centered woman of the fifties was no exception. The aim of the paper is to highlight that Sylvia Plath who at first relished the domination of her male counterparts, at the later stage of her life became a sworn enemy of male dominance and aggressively challenged the patriarchy. Her feminine angst transformed her from a lamb to a lioness hunting for men’s head.